1985
DOI: 10.1530/jrf.0.0750121
|View full text |Cite
|
Sign up to set email alerts
|

FSH influences follicle viability, oestradiol biosynthesis and ovulation rate in Romney ewes

Abstract: Summary. Injection of steroid-free bovine follicular fluid (bFF; 2 \m=x\5 ml s.c. 12h apart) into anoestrous ewes lowered plasma FSH concentrations by 70% and after 24 h had significantly (P < 0\m=.\01) reduced the number of non-atretic follicles (\ m=ge\ 1 mm diam.) without influencing the total number of follicles (\ m=ge\ 1 mm diam.) compared to untreated controls. Hourly injections of FSH (10 \g=m\g i.v. NIH-FSH-S12) for 24 h did not influence the number of non-atretic follicles but did negate the inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
3

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 24 publications
4
46
0
3
Order By: Relevance
“…A small slit was made in the follicle wall to allow the antral fluid to escape into a Petri dish, from where it was aspirated through a finely drawn-out Pasteur pipette, taking care not to remove clumps or sheets of granulosa cells. A known volume of the follicular fluid was added to 100 ml PBS and frozen at K20 8C for subsequent measurement of E 2 concentrations, the most reliable indicator of the health status of antral follicles over a wide range of sizes (McNatty et al 1985). The granulosa cells were recovered and counted by using haemocytometer.…”
Section: Dissection Of the Ovarian Folliclesmentioning
confidence: 99%
See 1 more Smart Citation
“…A small slit was made in the follicle wall to allow the antral fluid to escape into a Petri dish, from where it was aspirated through a finely drawn-out Pasteur pipette, taking care not to remove clumps or sheets of granulosa cells. A known volume of the follicular fluid was added to 100 ml PBS and frozen at K20 8C for subsequent measurement of E 2 concentrations, the most reliable indicator of the health status of antral follicles over a wide range of sizes (McNatty et al 1985). The granulosa cells were recovered and counted by using haemocytometer.…”
Section: Dissection Of the Ovarian Folliclesmentioning
confidence: 99%
“…red, pink or white) was recorded. For the purpose of this study, a healthy follicle was defined as one with i) visible thecal blood capillaries, ii) follicular fluid devoid of debris, iii) a pink-to red-coloured theca interna, iv) a normal-looking and intact oocyte-cumulus cell complex and v) more than 25% of the maximum number of granulosa cells for a given follicle size (McNatty et al 1985). Conversely, an atretic follicle was one to which any of these criteria did not apply.…”
Section: Pre-/post-natal Nutritionmentioning
confidence: 99%
“…In the present study, the increased ovulation rate followed treatment with relatively small amounts of follicular fluid for only 3 days after the start of luteolysis. Administration of FSH or substances with FSH-like activity will increase ovulation rate in sheep (Wright et al, 1981;Boland et al, 1983;Kelly et al, 1983;McNatty et al, 1985). Perhaps the elevated plasma concentrations of FSH and LH occurring on cessation of treatment allowed a greater than normal number of follicles to attain ovulatory maturity in synchrony in some ewes, hence the increased frequency of multiple ovulations.…”
Section: Follicular Characteristics After Treatment With Bffmentioning
confidence: 99%
“…In the present study, a significant correlation was found between mean plasma concentrations of FSH during the mid-luteal phase and the number of CL formed in the following cycle. Mean concentrations of FSH in ewes with 2 and 3 ovulations were well in excess of that required to increase the ovulation rate from 1 to 2 [17]. Therefore, increased concentrations of FSH, in response to 3α-diol-immunization are likely to be at least partially responsible for the increased ovulation rate in these ewes.…”
Section: Discussionmentioning
confidence: 90%
“…In this experiment, however, concentrations of FSH were significantly increased by 3α-diol immunization during the mid-luteal phase, a result similar to that reported in A4-immunized ewes by McNatty et al [15], who concluded that the increased FSH concentrations were at least partially responsible for the increased ovulation rate in A4-immunized ewes. It has been well documented that treatments with exogenous FSH [17][18][19] or treatments that i n c r e a s e e n d o g e n o u s F S H l e v e l s s u c h a s immunization against inhibin [21,22] or E2 [1,22], all increase ovulation rates in ewes. In the present study, a significant correlation was found between mean plasma concentrations of FSH during the mid-luteal phase and the number of CL formed in the following cycle.…”
Section: Discussionmentioning
confidence: 99%